2002
DOI: 10.1021/jp025650z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Adsorption of l-Cysteine on a Polycrystalline Silver Electrode by Surface-Enhanced Raman Scattering (SERS) and Surface-Enhanced Second Harmonic Generation (SESHG)

Abstract: The adsorption of L-cysteine (L-Cys) onto a polycrystalline silver electrode surface was investigated by in situ spectroelectrochemical methods. Surface-enhanced Raman spectroscopy (SERS) and surface-enhanced second-harmonic generation (SESHG) measurements were performed in a 0.2 M KCl solution in the presence and absence of L-Cys. The experimental results indicated that L-Cys strongly adsorbs onto silver and remains on the surface at potentials as negative as -900 mV (vs Ag/AgCl). A peak around -650 mV was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 38 publications
9
94
3
Order By: Relevance
“…This kind of reaction could be related to a Kolbe Mechanism (Vijh andConway 1967, Wang et al 2015), but this kind of behavior should be more expressed in alkaline media due to the higher reactivity of the deprotonated carboxyl; but interestingly, in acid media (pH 0), this reaction was more pronounced (Dourado et al 2017). This fact was explained by the structure of the first adsorbed species, which were different from those reported for Au (Bieri and Bürgi 2005, Di Felice et al 2003, Di Felice and Selloni 2004 and Ag (Brolo et al 2002, Santos et al 2007, meaning that the carboxyl was away from the surface for Au and Ag at lower pH values and closer in alkaline media. The fact that on Pt the position of the carboxyl is the opposite can be due to its high affinity to H adsorption and catalysis, being the only one among the three electrodes to present a H UPD region.…”
Section: Oxidationcontrasting
confidence: 57%
See 1 more Smart Citation
“…This kind of reaction could be related to a Kolbe Mechanism (Vijh andConway 1967, Wang et al 2015), but this kind of behavior should be more expressed in alkaline media due to the higher reactivity of the deprotonated carboxyl; but interestingly, in acid media (pH 0), this reaction was more pronounced (Dourado et al 2017). This fact was explained by the structure of the first adsorbed species, which were different from those reported for Au (Bieri and Bürgi 2005, Di Felice et al 2003, Di Felice and Selloni 2004 and Ag (Brolo et al 2002, Santos et al 2007, meaning that the carboxyl was away from the surface for Au and Ag at lower pH values and closer in alkaline media. The fact that on Pt the position of the carboxyl is the opposite can be due to its high affinity to H adsorption and catalysis, being the only one among the three electrodes to present a H UPD region.…”
Section: Oxidationcontrasting
confidence: 57%
“…DFT calculations predict the possibility of a small flux charge from Au to alkylthiol, and some XPS measurements observed Au(0) on the surfaces when the thiol SAM is formed, which was also observed for uncharged sulfur layers (Reimers et al 2016). The hydrogen bond network observed in the case of L-Cys adsorption (Brolo et al 2002, Hager andBrolo 2003) can be the reason for the stabilization of the SAM, contributing to the Au(0)-thyil system, which stabilizes and protects the surface, to the detriment of the Au(I)-thiolate one, which contributes to the dissolution of the surface (Chi et al 2017, Reimers et al 2016). This fact can be the reason why at pH 14 the adsorption of L-Cys onto Pt does not occur (Dourado et al 2017); the charged molecule does not favor the formation of a Metal-S bond with high covalent contribution, providing a more instable system.…”
Section: Adsorptionmentioning
confidence: 99%
“…10 After several minutes, the chloride anions are at least in part removed from the surface by successively adsorbed cysteine molecules in the most stable P H conformation, in which all three functional groups may immediately interact with the Ag and more COO -groups are situated close to the surface. Brolo et al 10 performed spectroelectrochemical experiments for L-cysteine solutions in 0.2 M KCl with surface-enhanced second-harmonic generation (SESHG) and SERS methods. They concluded that cysteine molecules change their conformation at -650 mV and claimed that cysteine adopts P C or P N conformation (called anti (II) and anti (I) in 10 ) at the silver electrode, dependent on the electrode potential.…”
Section: Resultsmentioning
confidence: 99%
“…However, SERS experiments reported in that paper were confined to neutral solutions and to a narrow spectral range (500-950 cm -1 ) covering mainly the C-S stretching vibrations. To verify the hypothesis about potential-controlled conformational transition, 10 the SERS spectra of cysteine adsorbed at a silver electrode were recorded at neutral, acidic (pH 2 and 3), and alkaline (pH 13) solutions within electrode potentials ranging from open circuit potential to -0.9 V. Because the SERS spectra showed small evolution within the first 10 min (see Figure 2 for comparison), each spectroelectrochemical measurement started about 15 min after immersion of the Ag electrode into the cysteine solution. Representative spectra for chosen potential values are displayed in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation